INFORMATION AND COMMUNICATION TECHNOLOGY TRAINING PROGRAM AT BDK MAKASSAR USING KIRKPATRICK'S CONCEPTUAL MODEL - Suaebah, Suaebah; Rasyid , Muhammad Nur Akbar; Mania, Sitti (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to evaluate the effectiveness of information and communication technology (ICT) training for government officials using Kirkpatrick's training evaluation model, which comprises four levels: reaction, learning, behaviour, and results. The background of this study is based on the need to improve the capacity of state officials in facing the demands of bureaucratic digitalisation and public services. The research method used was a quantitative approach with a survey design, supplemented by descriptive and inferential analysis. Data were collected through questionnaires administered to 120 respondents who were officials who had participated in ICT training programmes in various government agencies, as well as in-depth interviews with 15 training management officials to reinforce the quantitative results. The results show that at the reaction level, the majority of participants were satisfied with the training material, methods, and facilitators. At the learning level, there was a significant increase in the mastery of basic to advanced ICT skills. At the behavioural level, participants were able to implement the competencies they had acquired in their daily work, although there were still obstacles related to facilities and organisational support. At the outcome level, the training contributed positively to improving work efficiency and the quality of public services. In conclusion, Kirkpatrick model-based ICT training is effective in improving the capacity of government officials, but requires follow-up in the form of institutional support and strengthening of digital infrastructure.